Guru Agama Kristen Memiliki Peran Penting Untuk Membantu Muridnya Pengenalan Akan Firman Tuhan Serta Membangun Hubungan Dengan Tuhan Dalam Menghadapi Tantangan Kehidupan - Yemi Makesia Br Sembiring Depari; Dorlan Naibaho (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Christian teachers have an important responsibility in guiding students to know God's word and build a close relationship with God. This research aims to identify the role of Christian teachers in helping students face life's challenges through teaching based on spiritual and biblical values. The research was conducted using qualitative methods with a case study approach in one Christian school. The research results show that Christian religious teachers act as spiritual guides, role models and motivators for students to strengthen their faith, as well as provide solutions based on God's word in facing various life challenges. Thus, the role of Christian religious teachers is very strategic in forming students' characters who are spiritually and morally strong.